Anti-glaucoma potential of Heliotropium indicum Linn in experimentally-induced glaucoma - Kyei, Samuel (Eye Vis (Lond), 2015)
BACKGROUND: Heliotropium indicum is used as a traditional remedy for hypertension in Ghana. The aim of the study was to evaluate the anti-glaucoma potential of an aqueous whole plant extract of H. indicum to manage experimentally-induced glaucoma. METHODS: The percentage change in intraocular pressure (IOP), after inducing acute glaucoma (15 mLkg(−1) of 5 % dextrose, i.v.), in New Zealand White rabbits pretreated with Heliotropium indicum aqueous extract (HIE) (30–300 mgkg(−1)), acetazolamide (5 mgkg(−1)), and normal saline (10 mLkg(−1)) per os were measured. IOPs were also monitored in chronic glaucoma in rabbits (induced by 1 % prednisolone acetate drops, 12 hourly for 21 days) after treatments with the same doses of HIE, acetazolamide, and normal saline for 2 weeks. The anti-oxidant property of the extract was assessed by assaying for glutathione levels in the aqueous humour. Glutamate concentration in the vitreous humour was also determined using ELISA technique. Histopathological assessment of the ciliary bodies was made. RESULTS: The extract significantly reduced intraocular pressure (p ≤ 0.05–0.001) in acute and chronic glaucoma, preserved glutathione levels and glutamate concentration (p ≤ 0.01–0.001). Histological assessment of the ciliary body showed a decrease in inflammatory infiltration in the extract and acetazolamide-treated group compared with the normal saline-treated group. CONCLUSION: The aqueous whole plant extract of Heliotropium indicum has ocular hypotensive, anti-oxidant and possible neuro-protective effects, which therefore underscore its plausible utility as an anti-glaucoma drug with further investigation.